PENGARUH PEMBERIAN INSULIN-LIKE GROWTH FACTOR-I (IGF-I) DARI SERUM KUDA CROSSBREED BUNTING TERHADAP FOLIKULOGENESIS MENCIT (Mus musculus) - Abdullah, Abdullah; Restiadi, Tjuk Imam; Lastuti, Nunuk Dyah Retno; Damayanti, Tita; wurlina, wurlina; Safitri, Erma (Ovozoa: Journal of Animal Reproduction, 2018)
The purpose of the research was to know the effect of Insulin-Like Growth Factor-I (IGF-I) derived from pregnant crossbreed mare serum (PMS) in mice (Mus musculus) folliculogenesis. The subject of this research were 20 female mice. The research was arranged by Completely Randomized Design (CRD) with four treatments and five replications. The treatment were K0 = 10 ng/ml of physiological NaCl, P1 = 10 ng/ml of IGF-I PMS, P2 = 20 ng/ml of IGF-I PMS, and P3 = 40 ng/ml of IGF-I PMS. Observed variables are number of primary, secondary, tertiary and de Graff follicles. During the treatment the estrus cycle was also observed. The data of follicles number were analyzed by Analysis of Variance (ANOVA), followed by HSD (Honestly Significant Difference) test. The result showed that the addition of IGF-I PMS significantly affect (p<0,05) on increasing of the primary and secondary follicles number. The addition of IGF-I PMS 20 ng/ml and 40 ng/ml can increase the primary and secondary follicle significantly (p<0,05).